2014
DOI: 10.1093/ejo/cju012
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying patient adherence during active orthodontic treatment with removable appliances using microelectronic wear-time documentation

Abstract: The daily wear time of removable appliances during the active phase of orthodontic therapy can be routinely quantified using integrated microelectronic sensors. The relationship between orthodontist and patient seems to play a key role in patient adherence. Wear-time documentation provides the basis for more individualized wear-time recommendations for patients with removable appliances. This could result in a more efficient, shorter, and less painful orthodontic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
62
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 31 publications
4
62
2
9
Order By: Relevance
“…This is in line with the literature in which compliance never exceeds 7 to 9 hours of the prescribed 8 to 15 hours per day, [19][20][21][22][23][24] indicating that only nocturnal wear can be predicted with any degree of certainty. Indeed, Schäfer et al 24 found that compliance was only close to that required (ie, more than 12 hours per day) in 7% of patients, and Schott and Ludwig 22 emphasized that 25% of patients wore their appliance for much less The degree of compliance does not appear to be related to the type of appliance, as Schott et al 21 found comparably low compliance in both active (functional) and passive (Hawley retainer) appliances. Our data enabled us to confirm this conclusion because no statistically significant difference in compliance was observed between different types of intraoral devices or between intraoral and extraoral appliances.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is in line with the literature in which compliance never exceeds 7 to 9 hours of the prescribed 8 to 15 hours per day, [19][20][21][22][23][24] indicating that only nocturnal wear can be predicted with any degree of certainty. Indeed, Schäfer et al 24 found that compliance was only close to that required (ie, more than 12 hours per day) in 7% of patients, and Schott and Ludwig 22 emphasized that 25% of patients wore their appliance for much less The degree of compliance does not appear to be related to the type of appliance, as Schott et al 21 found comparably low compliance in both active (functional) and passive (Hawley retainer) appliances. Our data enabled us to confirm this conclusion because no statistically significant difference in compliance was observed between different types of intraoral devices or between intraoral and extraoral appliances.…”
Section: Discussionsupporting
confidence: 91%
“…Studies on the TheraMon compliance monitoring system show that compliance is invariably less than that requested by the orthodontist, [19][20][21][22][23][24] and our study in particular revealed a compliance of 8.6 6 2.9 hours per day when 13 hours' wearing time was prescribed. This is in line with the literature in which compliance never exceeds 7 to 9 hours of the prescribed 8 to 15 hours per day, [19][20][21][22][23][24] indicating that only nocturnal wear can be predicted with any degree of certainty.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Patients who had failed to show substantial progress and eventually discontinued TB treatment were excluded. Electronic wear time documentation using incorporated microsensors would have aided quantification of patient adherence to prescribed wear time, 31 though flaws in identifying specific temperature profiles have been described elsewhere. 32 When interpreting the results of TB studies that looked into incisor inclination changes, attention should be focused on methodologic issues like small sample size; 33 early treatment timing; 19 varying appliance wear protocols; 20,34 prolonged treatment, including retention phase; 19,25 and cephalometric evaluation after fixed appliances stage.…”
Section: Discussionmentioning
confidence: 99%